APAKAH PEMASARAN KONTEN DAN INOVASI PRODUK BERPENGARUH TERHADAP KEPUTUSAN PEMBELIAN RUMAH? STUDI KASUS: CUSTOMER PT HOME - Nur Khayati; Rayhan Gunaningrat; Triana (STKIP Subang, 2026)
Increasing competition in the subsidized housing industry requires developers to improve marketing strategies and product quality to encourage consumers’ purchase decisions. This study aims to analyze the effects of content marketing and product innovation on house purchase decisions among customers of PT HOME in Sukoharjo. The study employed a quantitative approach using a survey method. The population consisted of 409 consumers who had purchased subsidized housing from PT HOME, with a sample of 84 respondents selected using purposive sampling. Data were collected through a five-point Likert-scale questionnaire and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 4.0. The results show that content marketing has a positive and significant effect on purchase decisions, with a path coefficient of 0.228 and a p-value of 0.032. Product innovation also has a positive and significant effect on purchase decisions, with a path coefficient of 0.517 and a p-value of 0.000. Product innovation has a stronger effect than content marketing. These findings indicate that house purchase decisions are influenced not only by the quality of marketing information but also by the added value offered through product innovation. Practically, PT HOME should improve the quality and accessibility of its marketing content while continuously developing housing products that meet consumers’ needs.